In-situ observation of Asian pollution transported into the Arctic lowermost stratosphere - Roiger, Anke; Schlager, Hans; Schäfler, Andreas; Huntrieser, H.; Scheibe, M.; Aufmhoff, Heinfried; Cooper, Owen R.; Sodemann, Harald; Stohl, Andreas; Burkhart, John; Lazzara, Matthew; Schiller, Cornelius; et al. (Copernicus, 2011)
On a research flight on 10 July 2008, the German research aircraft Falcon sampled an air mass with unusually high carbon monoxide (CO), peroxyacetyl nitrate (PAN) and water vapour (H2O) mixing ratios in the Arctic lowermost stratosphere. The air mass was encountered twice at an altitude of 11.3 km, ~800 m above the dynamical tropopause. In-situ measurements of ozone, NO, and NOy indicate that this layer was a mixed air mass containing both air from the troposphere and stratosphere. Backward trajectory and Lagrangian particle dispersion model analysis suggest that the Falcon sampled the top of a polluted air mass originating from the coastal regions of East Asia. The anthropogenic pollution plume experienced strong up-lift in a warm conveyor belt (WCB) located over the Russian east-coast. Subsequently the Asian air mass was transported across the North Pole into the sampling area, elevating the local tropopause by up to ~3 km. Mixing with surrounding Arctic stratospheric air most likely took place during the horizontal transport when the tropospheric streamer was stretched into long and narrow filaments. The mechanism illustrated in this study possibly presents an important pathway to transport pollution into the polar tropopause region. ISSN:1680-7324 ISSN:1680-7375